Three-dimensional simulation for left ventricular assist device implantation in a small patient with chest wall deformity. (5th September 2018) - Yajima, Shin; Toda, Koichi; Tsukiya, Tomonori; Sawa, Yoshiki
Abstract: The rate of patients requiring left ventricular assist device (LVAD) implantation remains at a pace exceeding 2000 per year worldwide. Children and small adult patients, with a body surface area <1.5 m 2, are at a disadvantage for receiving an implantable LVAD because of its large pump size. Preoperative simulation of the results of various LVAD implantation methods and devices in such challenging cases will be helpful for surgeons. Herein, we introduce a preoperative LVAD simulation method using image processing software and present a case in which we obtained satisfactory results.